CONCEPTUAL PRINCIPLES OF THE FORMATION OF THE INCLUSIVE LABOR MARKET IN UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. In the conditions of war, Ukraine faces numerous challenges that affect the socio-economic situation and the functioning of the labor market. At the same time, the formation of an inclusive labor market, which is able to provide equal opportunities for all citizens, including vulnerable groups of the population, which will contribute to social cohesion and economic stability of the country, becomes particularly relevant. This requires the formation of conceptual approaches to the creation of an inclusive labor market in Ukraine, taking into account the peculiarities of wartime and the challenges facing the country.The purpose of the article. The purpose of the study is to determine the conceptual foundations of the formation of an inclusive labor market in Ukraine in wartime conditions based on the identification of the main challenges for attracting vulnerable population groups to the labor market and the development of ways to overcome them in order to ensure the social and economic stability of the state.Methods. The research methodology is based on a comprehensive approach, which includes the analysis of scientific literature, regulatory and legal framework and statistical data. The research uses methods of comparative analysis to determine barriers in the labor market, a systematic approach to determine the conceptual foundations of inclusiveness, and a method of logical generalization to determine practical ways to solve the identified problems.Results. The article identifies the need for the formation of an inclusive labor market in Ukraine in the conditions of war, when socio-economic instability affects access to employment for various population groups. The main barriers to the participation of vulnerable population groups in the labor market, including veterans, internally displaced persons, people with disabilities, youth and women, have been identified. The analysis of the modern legal framework showed that there is currently a shortage of state support tools for their employment. The importance of cooperation between the state, business and the public sector to create equal employment opportunities has been proven. Conceptual approaches to the formation of an inclusive labor market are defined: implementation of professional retraining programs, development of social entrepreneurship and adaptation of workplaces. The need for the formation of a state policy aimed at ensuring equal access to the labor market for all population groups and strengthening the economic stability of Ukraine has been proven.Conclusions. The importance of the formation of an inclusive labor market in Ukraine as a key element of socio-economic stability in the conditions of war has been proven. The proposed conceptual principles ensure the expansion of opportunities for vulnerable population groups, the reduction of unemployment and the increase of social cohesion.
Keywords: labor market, inclusive development, martial law, economic security, employment, socio-economic stability.